2022
DOI: 10.3390/app122211376
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Task Performance and Human Vigilance in Different Noise Environments

Abstract: Twelve healthy male college-age students were recruited to investigate the effects of different noise exposure conditions on complex task performance and vigilance. During each noise exposure, the Multi-Attribute Task Battery (MATB) with low, medium, and high mental workloads were conducted in the order designated by the Latin square method. Meanwhile, a psychomotor vigilance test (PVT) was used to evaluate human vigilance. Heart rate variability (HRV) signals were also collected while participants performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The computerized cognitive tests were performed in the following sequence: the PVT task, the 2-back task, the Stroop task, the mental arithmetic task, the hearing threshold test, the duration discrimination task, and the frequency discrimination task. Performances in the operational task were analyzed in a previous study [27,43]; these data, however, are not analyzed in this paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The computerized cognitive tests were performed in the following sequence: the PVT task, the 2-back task, the Stroop task, the mental arithmetic task, the hearing threshold test, the duration discrimination task, and the frequency discrimination task. Performances in the operational task were analyzed in a previous study [27,43]; these data, however, are not analyzed in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of noise level on human vigilance was also widely investigated due to the high vigilance requirement for operators in automatic human-machine systems. Yang et al [27] reported that higher noise sound pressure levels impair human vigilance, which was reflected in a lower mean sample entropy of heart rate variability and worse performance on a psychomotor vigilance test. Mohammad et al [28] found that mental workload and visual/auditory attention were significantly reduced when the participants were exposed to noise at a level of 95 dBA.…”
Section: Noise Exposure and Human Cognitive Performancementioning
confidence: 99%
See 1 more Smart Citation